Historical compliance rates for providing postoperative radiotherapy in oral cavity squamous cell carcinoma. Issue 10 (9th April 2016) - Hinther, Ashley; Nakoneshny, Steven C.; Dort, Joseph C.; Chandarana, Shamir P.; Matthews, T. Wayne
Abstract: Background: In 2014, Alberta Health Services released guidelines for treating oral squamous cell carcinoma (OSCC). Methods: A retrospective analysis was performed to assess the historical selection of patients with OSCC for postoperative radiotherapy (PORT) in a prospectively collected cohort of patients being treated with primary surgery. The primary outcome was compliance with the 2014 Alberta Health Services (AHS) guideline recommendations for PORT. The secondary outcome was the selection of PORT according to published pathological indications of high, intermediate, and low risk of recurrence. Reasons for discordance were analyzed. Result: Noncompliance with the new AHS guidelines and published indications for PORT was observed in 17% and 30% of cases, respectively. The reasons for discordance with published indications included: clinician decision ( n = 41) and unmodifiable factors ( n = 17). Conclusion: The impact of noncompliance on patient outcomes is being studied. The effect of the publication of the guidelines on selection for PORT going forward will be monitored. © 2016 Wiley Periodicals, Inc. Head Neck 38: First–1529, 2016